Potential use of germicides in vase solutions for gladiolus 'White Friendship' - Cásares, Maria Carolina; Mattiuz, Ben-Hur [UNESP]; Muniz, Ana Carolina Corrêa [UNESP]; Mattiuz, Claudia Fabrino Machado (Lepidus Tecnologia, 2017)
Gladiolus (Gladiolus x hortulanus) is one of the most important crops for cut flowers worldwide, however having a short longevity. Usually, stems are harvested at the bud stage and need water and carbohydrates to support inflorescence development and to ensure flower quality. Vase solutions can supply these elements. However, sugars may benefit bacterial proliferation, which eventually can block xylem vessels. Bactericides potentially inhibit microorganism proliferation and new compounds are being tested constantly. This experiment was conducted to evaluate 'White Friendship' cut gladiolus performance in vase solutions with sodium dichloroisocyanurate dihydrate (Na-DCC), 8-hydroxyquinoline (8-HQ) or polymeric biguanide (PB). Inflorescences harvested at commercial maturity were placed in distilled water with 4% w/v of sucrose plus the germicides and kept under ambient conditions. Vase life, inflorescence postharvest development, fresh mass, membrane stability index and water relations were evaluated. There were no visual symptoms of toxicity in the treatments. The highest values of vase life, fully-open flowers, fresh mass and water balance were obtained with the Na-DCC treatment. Inflorescences treated with 8-HQ exhibited the highest values of solution uptake and wilting flowers. PB had a limited effect in gladiolus postharvest since the obtained results were similar to the sucrose alone. There was no effect of germicides on membrane stability index and its reduction was due to flower senescence progress only. Vase solution with Na-DCC plus sucrose improved water balance, increased open flowers, reduced wilting of flowers and fresh mass loss. Therefore, vase solutions with sucrose 4% w/v and Na-DCC enhance postharvest quality of cut gladiolus inflorescences.
Keywords: Antimicrobial agents; Flower quality; Postharvest conservation; Vase life